Human resource management in small and medium-sized enterprises in the Czech Republic - Fejfarová, Martina; Urbancová, Hana (Univerzita Pardubice, 2016)
Human resource management is a crucial factor that determines the success of small and medium-sized enterprises in the market and its competitiveness. Small and medium-sized enterprises in the Czech Republic form a significant group of employers in the Czech Republic since they employ two thirds of employees out of the total number of the work force and represent over 99% of the overall number of active business entities. The main objective of the article is to evaluate the level of human resource management in small and medium-sized enterprises in the Czech Republic. Partial objectives of the article are to define a human resource management profile of small and medium-sized enterprises in the Czech Republic and to test dependencies between selected qualitative features. The data (n = 499) was collected by means of a questionnaire technique. The results of the survey confirmed important human resource management internal factors (the size of the enterprise, the position of the HR manager in top management and the existence of the HR department) and helped to define the human resource management profile of small and medium-sized enterprises in the Czech Republic.
Keywords: human resource management; HRM activities; small and medium-sized enterprises; Czech Republic; survey; J24; M12; O15